The underdetermined knowledge-based theory of the MNC - Fransson, Anders; Håkanson, Lars; Liesch, Peter W (Journal of International Business Studies, 2011)
In this note we revisit two core propositions of the knowledge-based view of the firm found in the seminal work of Kogut and Zander: (1) that multinational corporations (MNCs) exist because transfers and re-combinations of knowledge occur more efficiently inside MNCs than between MNCs and third parties; and (2) that the threat of opportunism is not necessary, although it may be sufficient, to explain the existence of the MNC. Their knowledge-based view shifted the conceptualization of the firm from an institution arising from market failure and transaction costs economizing to a progeny of superior knowledge governance. We question these conclusions, arguing that firms are but one of the many types of “epistemic communities” possessing and nurturing procedural norms, identity, and the cognitive, linguistic and reflexive attributes conducive to efficient exchange and re-combination of knowledge among their members. Important insights may be gained by applying the concept of epistemic communities implicit in the knowledge-based perspective beyond firm-level hierarchies.